PENGARUH PEMBELAJARAN KONTEKSTUAL BERBASIS ETNOMATEMATIKA TERHADAP PEMAHAMAN KONSEP TRANSFORMASI GEOMETRI SISWA KELAS IX SMPN 1 KEDUNGJAJANG - Lestari, Putri Dwi; Ridho'i, Mohammad; Abdul Halim, Fahmi; Sailatur Rizkiyah, Diva Aurora (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The limited understanding of geometric transformation concepts highlights the need to link mathematics instruction with real-world experiences. This study aimed to determine whether ethnomathematics-based contextual learning-utilizing the architecture of the KH. Anas Mahfud Grand Mosque-had a significant effect on the conceptual understanding of 9th-grade students at SMP Negeri 1 Kedungjajang. A quasi-experimental design was employed, specifically the Posttest-Only Control Group Design. Purposive sampling was used to select the participants, resulting in Class IX C (25 students) serving as the experimental group and Class IX B (25 students) as the control group. Data were collected via an essay-based posttest and documentation, then analyzed using tests for normality and homogeneity, followed by an independent sample t-test. The results revealed a significance value (Sig. 2-tailed) of 0.000 (p < 0.05), with the experimental group achieving a higher mean posttest score (88.20) compared to the control group (68.96). These empirical findings demonstrate that implementing a local culture-based contextual learning strategy has a significant, positive impact on improving students' mastery of geometric transformation concepts